The Effect of Area Reduction of Forward Die on the Combined Forward- Backward Extrusion Process - Muhamed, Jamal Hussien; Jweeg, Muhsin Jabur; Saleh, Ali Hassan (Nahrain University College of Engineering Journal, 2009)
The effect of reduction area for flat and conical dies in forward-backward extrusion process was investigated experimentally using flat punches with three reduction areas (0.305,0.444,0.605), 0.444 with cone angles (60o,90o,120o) and polygonal punches (hexagonal and square).Three reduction areas of dies (0.395, 0.555, 0.691) are used. The results show that the extrusion load is effected with reduction area of flat dies more than conical dies when using cone and flat punches while the reduction area of conical dies affected with square punch more than hexagonal punch and this result was inversed with flat dies. The relative extrusion pressure P/ increases when the reduction area of conical and flat dies increases too for all punches, but this result contrasts with thesquare punch at conical dies.The less value of max. stress was found with cone punch of prism angle 120o among cone punches for conical dies except the die of reduction area (0.555) and the cone punch of 90o prism angle gave less max. stress with all flat dies. Flat punch of reduction area (0.444) among theflat punches gave less value of max. stress with all conical dies and flat die of reduction area (0.691).